Calculating the absolute adsorption of high-pressure methane on shale by a new method - Luo Zuo; Tingxue Jiang; Haitao Wang (Adsorption Science & Technology)
Currently, many adsorption experiments of methane on shale have been done to understand adsorption characteristics of methane on shale, but those experiments’ pressure and temperature are far less than reservoir pressure and temperature; therefore, we carried out the experiments of methane adsorption on shale at 75.6°C and 95.6°C with 0–50 MPa pressure range to study the adsorption characteristics of shale under reservoir condition. We also build a new method to calculate the real (absolute) adsorption of methane on shale. Results present that the characteristics of excess adsorption isotherm under high pressure is different from the characteristics of excess isotherm under low pressure; adsorption obtained by adsorption experiment increases with pressure going up until reaching a peak and then declines with further increase in pressure. We build a new method to calculate the absolute adsorption by assuming that the adsorption phase volume approximately equals to the total volume occupied by adsorbed molecule, and the results calculated by our method show this method is reasonable and effective.